Bacillus anthracis strain differentiation based on SNP and VNTR loci - E. A. Anisimova; N. A. Fakhrutdinov; D. A. Mirgazov; E. A. Dodonova; I. A. Elizarova; M. E. Gorbunova; N. I. Khammadov; L. I. Zainullin; K. A. Osyanin (Вавиловский журнал генетики и селекции)
Bacillus anthracis is the anthrax causative agent. For its epidemiology, it is important not only to identify the etiological agent but also to determine the patterns of its evolution and spread. Modern methods of molecular biology make it possible to detect a number of genetic markers suitable for indicating and differentiating the strains of B. anthracis, including the loci arranged as variable number tandem repeats (VNTRs) and SNPs, one nucleotide-sized differences in the DNA sequence of the loci being compared. The objective of the present study was to examine the effectiveness of SNP analysis and PCR amplif ication of VNTR loci combined with the high-resolution amplicon melting analysis for identif ication and differentiation of the anthrax agent strains. In the study, seven strains of B. anthracis obtained from soil samples and animal carcasses were investigated using vaccine strain STI-1 as a reference. For molecular genetic characterization of these bacteria, analysis of 12 SNPs and variability analysis of eight VNTR loci were carried out. To detect the differences between the strains, their PCR product melting points were measured in the presence of the EvaGreen (Sintol, Russia) intercalating dye. For SNP detection, a PCR assay with double TaqMan probes was applied. It was found that the studied virulent strains, except for B. anthracis No. 1 and 3, could not be attributed to any phylogenetic subgroup of the anthrax agents. The proposed method made it possible to differentiate four out of the seven investigated strains. Strains No. 5–7 had identical SNP and HRM prof iles and, as a result, formed a single cluster. Our investigation has conf irmed that the proposed method can be successfully used for preliminary analysis of an epizootic situation in the case of anthrax.